Framing Analysis of Alleged Blasphemy Cases by Al-Zaytun Islamic Boarding School Leaders: Panji Gumilang on Detik.com and Republika.co.id Media for the July to August 2023 Period - Winda Winda; Wahyu Widiastuti; Dionni Ditya Perdana (Publikasi Indonesia, 2024)
Blasphemy is a significant and sensitive topic in the news, prompting mass media to allocate coverage to religious issues. This study utilizes qualitative methods, employing the framing model analysis of William A. Gamson and Andre Modigliani. The objective is to examine news concerning alleged blasphemy cases involving Panji Gumilang, the head of Al-Zaytun ponpes, as reported by Republika and Detik during the period from July to August 2023. Researchers scrutinized six news articles, three from Republika and three from Detik. The findings reveal that both Republika and Detik distinctly highlight ongoing investigations by law authorities into the blasphemy case attributed to Panji Gumilang. Republika's coverage primarily focuses on evidence exploration to gather information, reinforcing the report on the alleged blasphemy case for a smoother legal process and justice. In contrast, Detik examines the societal influence and impact of the blasphemy case. Meanwhile, Detik discussed the influence and impact of this blasphemy case on society. The reason for choosing the two media is because both have different backgrounds, Republika is a media born from the Muslim community that is more in-depth in news related to Islamic religious issues while Detik is a popular media whose reporting is neutral.